A Case Report: A Third/Fourth Branchial Pouch Anomaly Presented by Solid Thyroid and Lateral Cervical Neck Masses - Magda H. A. Nasreldin; Eman A. Ibrahim; Somaia A. Saad El-Din (SAGE Publishing, 2016)
Branchial pouch-derived anomalies may arise from remnants of the first, second, or third/fourth branchial arches. Branchial pouch-related structures are found within the thyroid gland in the form of solid cell rests, epithelial lined cyst with or without an associated lymphoid component, thymic and/or parathyroid tissue, and less commonly in the form of heterotopic cartilage. We present a rare case of left solid thyroid swelling nearby two cervical nodules in a seven-year-old female with a clinical diagnosis suggestive of malignant thyroid tumor with metastasis to the cervical lymph nodes. Histopathological examination revealed that it was compatible with third/fourth branchial pouch-derived anomaly composed of mature cartilage and thymic and parathyroid tissues for clinical and radiological correlations.